1991
DOI: 10.1159/000284690
|View full text |Cite
|
Sign up to set email alerts
|

Time Estimation and the Experience of Time in Endogenous Depression (Melancholia): An Experimental Investigation

Abstract: The importance of disturbances in time experience in endogenous depression (melancholia) has long been under discussion. In the present study alterations of time experience were examined by means of time estimation experiments. 25 endogenous depressive patients (according to ICD-9) underestimated prospectively a 30-second interval by 6 s, whereas 12 healthy controls overestimated this interval by more than 10 s. The results are based on eight successive measurements over a period of 2 days. In the endogenous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
5

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 12 publications
1
10
0
5
Order By: Relevance
“…This reliance on central resources is why time judgment performance is often used as an indicator of overall cognitive function. In fact, timing is so sensitive to changes in cognitive processing that distorted time perception is a defining feature of many altered states of consciousness (Block, 1979;Ludwig, 1966;Tart, 1975) and is considered to be a classic symptom of various psychopathological conditions (e.g., Hibbard, Migliaccio, Goldstone, & Lhamon, 1975;Kuhs, Hermann, Kammer, & Tolle, 1991;Lhamon & Goldstone, 1973). Not coincidentally, these conditions are associated with major changes in general executive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…This reliance on central resources is why time judgment performance is often used as an indicator of overall cognitive function. In fact, timing is so sensitive to changes in cognitive processing that distorted time perception is a defining feature of many altered states of consciousness (Block, 1979;Ludwig, 1966;Tart, 1975) and is considered to be a classic symptom of various psychopathological conditions (e.g., Hibbard, Migliaccio, Goldstone, & Lhamon, 1975;Kuhs, Hermann, Kammer, & Tolle, 1991;Lhamon & Goldstone, 1973). Not coincidentally, these conditions are associated with major changes in general executive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have failed to find any evidence of disturbed duration judgments for different levels of depression (Bech, 1975;Hawkins, French, Crawford & Enzle, 1988;Kitamura & Kumar, 1984;Mezey & Cohen, 1961;Munzel, Gendner, Steinberg & Raith, 1988;Prabhu, Agrawal & Teja, 1969;Wyrick & Wyrick, 1997). Other studies, by contrast, have found that depressive mood disrupts time judgments by causing time distortions and/or by reducing sensitivity to time (Bschor et al, 2004;Grinker, Glucksman, Hirsch & Viseltear, 1973;Kitamura & Kumar, 1982;Kuhs, Hermann, Kammer & Tolle, 1991;Msetfi et al, 2012;Mun- , 1988;Rammsayer, 1990;Sévigny, Everett & Grondin, 2003;Tysk, 1984;Wyrick & Wyrick, 1977). However, where time distortions have been observed, they have more often taken the form of temporal shortening, rather than the temporal lengthening described in depressive patients' statements (e.g.…”
Section: Subjective Experience Of Time's Passage and Affective Disordersmentioning
confidence: 96%
“…However, where time distortions have been observed, they have more often taken the form of temporal shortening, rather than the temporal lengthening described in depressive patients' statements (e.g. Bschor et al, 2004;Grinker et al, 1973;Kuhs et al, 1991;Tysk, 1984). For instance, Grinker et al (1973) found that depressed individuals underestimated time, and that this underestimation increased with the severity of their depression.…”
Section: Subjective Experience Of Time's Passage and Affective Disordersmentioning
confidence: 99%
“…He postulated mechanisms in the central nervous system responsible for the intergration of successive events into a subjectively experienced time unit of a few seconds. Time perception is frequently altered in depression [10,20]. The results warrant further studies investigating specifically changes of time perception and decribed motor phenomena in depression.…”
Section: Discussionmentioning
confidence: 69%